Articulation of Syaikhona Mohammad Kholil's Staff in Nahdlatul Ulama's Management - Mohammad Makki Nasir; Ahmad Ahmad (Journal of Nahdlatul Ulama Studies, 2022)
Verses 17-21 of Surah Thaha are the philosophical of establisment of Nahdlatul Ulama'. This verse came as a sign of Sheikhona Mohammad Kholil's message to KH. Hasyim Asy'ari through the intermediary of KH. As'ad Syamsul Arifin. This verse has strong articulation, both in the story of the Prophet Moses, the Prophet Muhammad, or geopolitics in the 1900s. This study wants to answer the challenge of this verse in the role of Nahdlatul Ulama' in facing various challenges of the transnationalism movement, globalization, radicalism, digital, the era of disruption, capitalism, modern colonialism, and other problems. This research method uses a blended methodology approach; historiographical, conceptual, and lexical-semantic research in dalalah lafzhiyyah in Arabic grammar. The research concludes that there is a vision of an articulate message contained in Syaikhona Mohammad Kholil's staff cue. Syaikhona Mohammad Kholil seemed to want to emphasize that the solution of Nahdlatul Ulama's in facing various challenges of the transnationalism movement, globalization, radicalism, digital, the era of disruption, capitalism, modern colonialism, and other problems have been contained in verses 17-21 of Surah Thaha. This solution, can be articulated in the managerial of the Nahdlatul Ulama organization. The managerial articulation that can be played by Nahdlatul Ulama' is in the form of planting a ideology and aqidah, independent economic management, good organizational leadership governance and the selection of sophisticated, beautiful and beautiful strategies and politics.